The antioxidant property, antimicrobial activity, and toxicity of the fractions from the ethanol extract of Leea aculeata Blume ("Mali-mali") leaves - Escobia, Ahmer Glenn M.; Uy, Mylene M. (2015)
This study evaluated the bioactivities of the hexane fraction (LaH), chloroform fraction (LaC), and aqueous fraction (LaA) of the leaves of the plant Leea aculeata Blume using the brine shrimp lethality test, DPPH radical scavenging activity, total phenolics content, total antioxidant activity and antimicrobial assays. Results show that only the aqueous fraction of the plant became rather toxic after 24 hours; the same fraction has relatively the highest DPPH radical scavenging activity, the highest total antioxidant activity and the highest total phenolics content. The antimicrobial screening indicated that the hexane fraction was inactive against all test microorganisms, the chloroform fraction was partially active towards S. aureus and active towards A. niger while the aqueous fraction LaA was active against S. aureus.
Keywords: Medicinal plants; Plant extracts